KECERDASAN EMOSI, ESTIM KENDIRI DAN KOMITMEN TERHADAP ORGANISASI: KESAN DAN PENGARUH DI KALANGAN PENJAWAT AWAM - Hj. Johar, Siti Sarawati (Journal of Techno-Social, 2017)
Emotional intelligence is currently getting growing attention and earning a spot in psychological studies. Emotional intelligence can affect employees’ commitment within an organization. Theoretical solution per se is not capable of dismantling issues in organizational psychology as it is closely associated with affective, cognitive and human behaviour in the workplace. In this study, the issues in the workplace is referring to emotional intelligence, self esteem and commitment to the organization. The specific objective of this study was to examine the impact of emotional intelligence among employees which may or may not influence the commitment to the organization through employees’ self esteem. A total of 162 civil servants in local authorities were selected as respondents. The measurement tools used in data collection were Emotional Intelligence Self-Description Inventory (EISDI), Rosenberg Self-Esteem Scale (RSES) and TCM Employee Commitment Survey Revised Version (ECS). Collected data were then analysed using hierarchical regression analysis. The findings showed that emotional intelligence has a direct impact on employees’ commitment. In fact, emotional intelligence also provide an indirect effect on employees’ commitment when self esteem as a mediator is controlled. Employees’ self esteem is later found to function as a partial mediator that affects the relationship between emotional intelligence and employees’ commitment. The most crucial finding discovered that emotional intelligence among employees may strive to become more relevant with the increasing commitment of employees when there is an element of self esteem as a mediating factor.